(U‐Th)/He Thermochronology and Zircon Radiation Damage in the South American Passive Margin: Thermal Overprint of the Paraná LIP?. Issue 10 (29th October 2018) - Hueck, Mathias; Dunkl, István; Heller, Beatrix; Stipp Basei, Miguel Angelo; Siegesmund, Siegfried
Abstract: New zircon and apatite (U‐Th)/He data (AHe and ZHe) from the crystalline basement of the South American passive margin in southern Brazil present a wide distribution of Phanerozoic apparent ages, recording its prerift evolution. Its geological significance can be investigated by modeling the influence of the accumulated radiation damages on the measured crystals in its He ages during a long upper crust residence. Despite the presence of a significant fault in the studied area, the samples essentially constrain a uniform thermal history for the entire study area. Zircon helium ages spread from 472 to 26 Ma and correlate strongly with the radioactive element content of the crystals. Although the region was probably covered by Paleozoic sediments of the Paraná Basin, the ZHe system experienced a more intense thermal overprint, most likely the onset of the Paraná Large Igneous Province (LIP), causing its dispersion. The nearby intrusion of a feeding system of the LIP, the Florianópolis Dyke Swarm, may have contributed for keeping geothermal gradients elevated for a period long enough to promote the observed reset. After the extrusion of the volcanism, the study area was probably covered by up to 2 km of basalt floods, imprinting temperatures above the AHe partial retention zone on the crystalline basement. These were eroded during rapid cooling between 75 and 55 Ma, as indicated by thermal modeling. Additional analyses with Raman spectroscopy were used for calculating radiation damage ages in the zircon crystals measured for (U‐Th)/He, resulting in a comparable set of ages. Key Points: Zircon He ages influenced by accumulated radioactive damage of crystals were partially reset by Cretaceous Paraná LIP Apatite He ages were completely reset and record a cooling event between 75 and 55 Ma by erosion of an up to 2‐km thick cover layer Raman spectroscopy‐based zircon radiation damage ages are comparable to He ages